1984
DOI: 10.1128/jcm.19.3.380-382.1984
|View full text |Cite
|
Sign up to set email alerts
|

Rapid confirmatory identification of Neisseria gonorrhoeae with lectins and chromogenic substrates

Abstract: A group of five tests utilizing wheat germ and soybean lectins and chromogenic substrates (orthonitrophenyl- ,-D-galactopyranoside, gamma-glutamyl-3-naphthylamide, and prolyl-3-naphthylamide derivatives) was used as a rapid (30-min) method for the identification of Neisseria gonorrhoeae. The rapid method agreed with Minitek test results for all 126 N. gonorrhoeae isolates and all 39 nongonococcal isolates tested. Soybean lectin was useful for the identification of rare strains (4 of 126) of N. gonorrhoeae whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…), Philip and Garton (4) found that 1 of 22 strains of N. meningitidis that they tested was negative for GAP, while Janda et al (3) found 5 of 172 N. meningitidis isolates negative for GAP. PAP-positive N. meningitidis isolates have also been reported by Yajko et al (7), who found 3 of 7 isolates positive, and by D'Amato et al…”
supporting
confidence: 54%
“…), Philip and Garton (4) found that 1 of 22 strains of N. meningitidis that they tested was negative for GAP, while Janda et al (3) found 5 of 172 N. meningitidis isolates negative for GAP. PAP-positive N. meningitidis isolates have also been reported by Yajko et al (7), who found 3 of 7 isolates positive, and by D'Amato et al…”
supporting
confidence: 54%
“…The Gonochek Il test (Du Pont Co., Wilmington, Del. ), which has also been described previously, is based on the differential utilization of three chromogenic substrates (5-bromo-4-chloro-3-indoyl-3-D-galactopyranoside, -y-glutamyl-para-nitroanilide, 3-niapthyl amino acid derivative) by Neisseria species (6,14,21,25,26). The microbial identification tubes were supplied with the kit.…”
Section: Minitek the Minitek Kit (Miniaturized Microorganismmentioning
confidence: 99%
“…Rapid identification of Neisseria gonorrhoeae may be accomplished by several diverse methods. The methods include carbohydrate utilization with preformed enzymes or enzymes formed during growth (5,8,12,15,20) and immunological (4,7,10,13), chromogenic (2,19), and radiometric (16) procedures. Immunological procedures include coagglutination with polyclonal (11) (Phadebact Gonococcus Test; Pharmacia Diagnostics, Piscataway, N.J.) and murine monoclonal (9) (Gono Gen; New Horizons Diagnostics, Columbia, Md.)…”
mentioning
confidence: 99%